Peran Public Relations Menangani Keluhan Pelanggan Perumahan Kyra Residence 3 Bekasi - Helmi Azahari; Endah Fantini; Feri Candra Ardianto (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2025)
This study aims to determine the communication strategy employed by the Public Relations department of PT Purnama Mulia Properti in handling customer complaints at Kyra Residence 3, Bekasi, West Java, using the concept of Excellence Theory in Public Relations. Mapping of customer complaints is carried out based on the Situational Theory of Publics. This theory can identify the public, allowing it to create public categories based on the communication behaviour of individuals and the effects of communication received by those individuals. Customer complaints often arise due to construction delays, technical issues, and limited facilities. The analysis was conducted using the POAC method (Planning, Organising, Actuating, Controlling) and the SERVQUAL model (Tangibles, Reliability, Responsiveness, Assurance, and Empathy). The study's results found that PT Purnama Mulia Properti's Public Relations applies the concept of Excellence Theory of Public Relations through responsive, empathetic, and transparent communication on digital channels, with a quick response as an effort to mitigate the negative impact of its services on customers. POAC is reflected in structured planning, team coordination, solution-oriented actions, and evaluation. Meanwhile, SERVQUAL highlights responsiveness and empathy as the strongest dimensions. Effective complaint handling has been proven to enhance a company's image and foster increased customer loyalty. Penelitian ini bertujuan mengetahui strategi komunikasi Public Relations PT Purnama Mulia Properti dalam menangani keluhan pelanggan di Kyra Residence 3 Bekasi, Jawa Barat dengan menggunakan konsep Excellence Theory of Public Relations. Pemetaan keluhan pelanggan dilakukan berdasarkan Situational Theory of Publics. Teori ini dapat mengidentifikasi publik sehingga dapat membuat kategori publik berdasarkan perilaku komunikasi dari individu dan efek komunikasi yang diterima individu tersebut. Keluhan pelanggan terjadi akibat keterlambatan konstruksi, masalah teknis, dan keterbatasan fasilitas. Analisis dilakukan dengan menggunakan metode POAC (Planning, Organizing, Actuating, Controlling) dan model SERVQUAL (Tangibles, Reliability, Responsiveness, Assurance, Emphaty). Dari hasil penelitian ditemukan bahwa Public Relations PT Purnama Mulia Properti menerapkan konsep Excellence Theory of Public Relations berupa komunikasi yang responsif, empatik, dan transparan melalui saluran digital, dengan tanggapan yang cepat sebagai upaya untuk mengurangi dampak negatif layanan kepada pelanggan. POAC tercermin dalam perencanaan terstruktur, koordinasi tim, tindakan berorientasi solusi, dan evaluasi. Sementara SERVQUAL menyoroti responsivitas dan empati sebagai dimensi terkuat. Penanganan keluhan yang efektif terbukti memperkuat citra perusahaan dan meningkatkan loyalitas pelanggan.